THE ANALYSIS OF PURSE SEINE FISHING GEAR AT THE BELAWAN OCEAN FISHERIES PORT, MEDAN, NORTH SUMATRA PROVINCE - Ahmat Hamonangan Rambe; Hendrik Hendrik; Trisla Warningsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT        The research on the Purse Seine fishing gear business was conducted on May 25 to June 8, 2018 at Belawan Ocean Fisheries Port (PPS), Medan City, North Sumatra Province. The purpose of this study is to find out how much investment, business feasibility, and sensitivity analysis of the Purse Seine fishing gear business are mini-sized 30 GT, medium 50 GT and 88  large. The number of respondents taken as many as 15 people where each size of the boat was taken by five people, one owner, one captain and three crew members               Based on the results of the study, it was found that the total investment business of the Purse Seine fishing gear was 30 GT in the amount of IDR. 1,030,276,000 and the Purse seine was 50 GT in the amount of IDR. 1,382,105,000, while the Purse Purse in large was 88 GT in the amount of IDR. 1,888. 635,000. NPV value of ship 30 GT is IDR.1,187,774,957, BCR of 1.23 and IRR of 40.95% of NPV value of medium-sized vessel is 50 GT of IDR.1,821,572,870, BCR of 1.25 and IRR of 46.39% while the NPV value of a large ship is 88 GT at IDR.2,607,345,034, BCR of 1.31 and IRR of 48.09%. Thus the business is profitable and feasible to develop. From the results of the sensitivity analysis calculations carried out for 10 years of business in scenario 3, costs are increased by 10% and production is reduced by 10% BCR = 1 means that the 30 GT ships only break even, that is not for and no loss.   Keywords:Purse Seine 30 GT Purse Seine 50 GT, Purse Seine 88 GT, BusinessFeasibility.